MANAJEMEN MASJID BERBASIS NILAI-NILAI INKLUSI SOSIAL DI KALIMANTAN TIMUR - Agustin, Riska Dwi; Liandra, Aru Arafi; Afiyah, Nur; Al Mughni, Muhammad (Jurnal Manajemen Dakwah, 2024)
This research is a qualitative study that prioritizes social values of inclusion in society through the management of mosques. The religious activities carried out in the mosque should be based on the principles of social inclusion that hold firmly to enhance the role of the individual in society. A society consist of diverse levels, gender differences and social classes can be an opportunity and a challenge in managing a mosque that is notable as a place of Islamic worship. The method used in this research is Descriptive Analysis by collecting data through observations, interviews and documentation. The results of this study show that the mosques located in Eastern Kalimantan, especially the Great Ulil Ijtihad Mosque and Jami’ Al Aqabah Mosque, are mosques that implement social inclusion management. This is demonstrated by the numerous social empowerment activities and the involvement of women in their religious activities.Keywords: Inclusion; Social; Mosque Management